Search for deconfinement in NA49 at the CERN SPS - Seyboth, Peter; Afanasiev, S.V.; Antičić, Tome Barna, D.; Bartke, J. Barton, R.A.; Betev, L. Bialkowska, H.; Billmeier, A. Blume, C.; Blyth, C.O. Boimska, B.; Botje, M. Bracinik, J.; Bramm, R. Brun, R.; Buncic, Predrag Cerny, V.; Chvala, O. Cramer, J.G.; Csato, P. Dinkelaker, P.: Eckardt, V.; et al. (2003)
Experiment NA49 at the Cern SPS uses a large acceptance detector for a systematic study of particle yields and correlations in nucleus-nucleus, nucleon-nucleus and nucleon-nucleon collisions. Preliminary results for Pb+Pb collisions at 40, 80 and 158 A*GeV beam energy are shown and compared to measurements at lower and higher energies.
Projekt MZOS
ENG